DESIGN AND ANALYSIS OF AN AXIAL FLUX PERMANENT MAGNET GENERATORS WIND TURBINE FOR AUTOMATIC STACKING CRANES - Maharani, Aisyah Aira Putri; Wahid, Muhamad Rizalul; Gianti, Mahmudah Salwa; Mulya, Tri Seda; Rahayuningtyas , Ari (Jurnal Rekayasa Mesin, 2025)
Automatic Stacking Cranes are indispensable tools in modern ports that can transfer containers between the landside and the waterside. These cranes are powered by electricity and consume significant amounts of energy to meet annual production demands. This substantial electricity consumption often strains the port's power grid during voltage and current fluctuations, which can destabilize the ASC's power supply. Wind turbines offer a promising alternative energy source to address these problems. This study delves into the analysis of the optimal Axial Flux Generator structure for wind turbines and calculates the associated energy losses to determine the feasibility of a wind turbine system capable of supporting the ASC's power demands. The findings reveal that employing an AFG-based wind turbine can generate the required 88,497 Watts of power for the ASC, with an average rotational speed of 1,655 rpm. This represents an annual electricity cost saving for the port of approximately 39,701,029 Rupiah.